The Impact of Fiscal Policy on Macroeconomic Conditions in Pakistan: Insights from a Structural Vector Autoregression Analysis - Sarnaila Sharif; Saima Nawaz (Business Review, 2024)
This article explores the relationship between fiscal policy and macroeconomic conditions in Pakistan using a robust Structural Vector Autoregression (SVAR) model. Since fiscal shock has the tendency to put a constraint on the future path of government spending and taxes, as the intertemporal budget constraint holds. This element has been missed in most of the VAR studies. This study extends Structural Framework by incorporating the dynamic nature of public debt in analyzing fiscal policy shocks. Our investigation focuses on estimating the responses of output, inflation, and debt interest payments to changes in government spending and taxes, while keeping track of the debt dynamics in the country. Our findings reveal the pivotal role of fiscal policy in shaping Pakistan's macroeconomic landscape. Government expenditure shocks have a positive impact on output, driving economic growth. However, this expansionary effect is accompanied by higher inflation, requiring careful policy considerations. In contrast, tax shocks have a negative and insignificant influence on output and inflation. Importantly, both government spending and tax shocks contribute to an increase in the debt ratio, emphasizing the importance of sustainable debt management for long-term economic stability.